Pelatihan Pemanfaatan Ban Bekas sebagai Pondasi Tahan Gempa di Desa Jenggala, Kabupaten Lombok Utara: Training on the Utilization of Used Tires as Earthquake-Resistant Foundations in Jenggala Village, North Lombok Regency - Sulistyowati, Tri; Agustawijaya, Didi Supriyadi; Eniarti, Miko; Muchtaranda, Ismail Hoesain; Setiawan, Agustono; Ngudiyono, Ngudiyono (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Jenggala Village is one of the villages in North Lombok Regency that was affected by the 2018 Lombok earthquake. Most damage to buildings and houses was caused by noncompliance with earthquake-resistant building standards. As the lower structure, the foundation is essential to distribute the structure's load, preferably given a layer that dampens vibrations. Used tires are an alternative material that can reduce seismic vibrations and be used as an earthquake-resistant house foundation. This community service project aims to raise public awareness about earthquake-resistant houses by using used tires as a foundation to reduce seismic vibrations. The methods used in this service activity are the lecture approach, discussion, question-and-answer sessions, and demonstrations with the foundation model made from used tires. The approach used is a participatory approach that is oriented towards efforts to increase community participation. The preparation stage, the implementation stage, and the evaluation stage are the activity stages. Based on the results of the community service activities, it was shown that the participants understood the training material for making earthquake-resistant foundations from used tires because the material was easy to obtain and very easy to manufacture. Partners have high motivation to participate in training. They are willing to share the training results with other community members so that using used tires as earthquake-resistant house foundations can support the post-earthquake rehabilitation and reconstruction process in all earthquake-affected areas in North Lombok Regency.